Finite Element Analysis-Based Vertebral Bone Strength Prediction Using MDCT Data: How Low Can We Go? - Rayudu, Nithin Manohar; Subburaj, Karupppasamy; Mei, Kai; Dieckmeyer, Michael; Kirschke, Jan S.; Noël, Peter B.; Baum, Thomas (Frontiers in Endocrinology, 2020)
OBJECTIVE: To study and compare the effect of dose reduction strategies (tube current reduction and sparse sampling) in multidetector computer tomography (MDCT) on vertebral bone strength prediction using finite element (FE) analysis for fracture risk assessment. METHODS: Routine MDCT data covering lumbar vertebrae of 12 subjects (6 male; 6 female; 74.70±9.13 years old) were included in this study. Sparse sampled and virtually reduced tube current based MDCT images were computed using statistical iterative reconstruction (SIR) with 50%, 25%, and 10% of the original projections and tube current, respectively. Subject-specific static non-linear FE analyses were performed on vertebra models (L1, L2, and L3) 3D-reconstructed from those dose-reduced MDCT images to predict bone strength. Bland-Altman plots, root mean square coefficient of variation (RMSCV), and coefficient of correlation (R2) were calculated to determine the variation in the FE-predicted strength for dose reductions, using standard dose-based strength as the reference. RESULTS: FE-predicted failure loads were not significantly affected by upto 90% dose reduction through sparse sampling (R2=0.93, RMSCV=8.6% for 50%; R2=0.89, RMSCV=11.90% for 75%; R2=0.86, RMSCV=11.30% for 90%) and upto 50% dose reduction through tube current reduction method (R2=0.96, RMSCV=12.06%). However, further reduction in dose, with tube current reduction method, affected the ability to predict the failure load accurately (R2=0.88, RMSCV=22.04% for 75%; R2=0.43, RMSCV=54.18% for 90%). CONCLUSION: Results from this study suggest that a 90% reduction in radiation dose through sparse sampling and 50% reduction through reduced tube current can potentially be used for predicting vertebral bone strength. Our findings suggest that spare sampling-based method performs better than tube-current reduction method in generating images required for FE-based bone strength prediction models.